IMPLEMENTASI LOAD BALANCING DENGAN METODE BUBBLE SORT STUDI KASUS PENGISIAN KRS DI STTA - Hidayat, Rahmad; Basukesti, Agus; Indrianingsih, Yuliani (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2013)
The increase o f request brings large traffic to networks especially to data centers, large enterprises and portal websites. In addition, server provides more and more information by using applications. Most servers have to provide all-day services, and any service interruption or key data loss in communication will result in business loss. All these require high performance and high reliability on application services. However, the increase of server processing speed and memory access speed is greatly lower than that o f the network bandwidth and applications. In addition, the increase o f network bandwidth makes server resource consumption more serious. Therefore, the servers become the network bottleneck, and the traditional single device mode becomes the network failure point. Load balancing (LB) comes to provide a good solution by providing multiple servers form a server cluster, with each server providing the same or similar services. A load balancing application is managed at the front end o f the server cluster to distribute user requests in the server cluster according to pre-configured load balancing rules, provide services, and maintain the servers. Load balancing bring good advantage such as bring faster application, low cost, the available resources will not be wasted, and no high-end devices are needed for the new resources. It is expandability. When services are increasing, the system can satisfy the needs by adding servers, without affecting the existing services and reducing service quality. Load balancing also has high reliability. When a server fails, the LB application or LB device redistributes user requests to other servers in the same cluster, ensuring uninterrupted services.